2011
DOI: 10.2478/s11658-011-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

The determination of changes in the expression of genes for selected specific transcriptional factors in in vitro ductal breast cancer cells under the influence of paclitaxel

Abstract: Abbreviations used: Bak -BCL2-antagonist/killer; Bax -BCL2-associated X protein; Bcl-2 -B-cell CLL/lymphoma 2; BRCA1 -breast cancer type 1 susceptibility protein; cDNAcomplementary deoxyribonucleic acid; CTCF -CCCTC-binding factor (zinc finger protein) CtIP -retinoblastoma binding protein 8; DCIS -ductal carcinoma in situ; DMSO -dimethyl sulfoxide; dNTPs -deoxynucleotide triphosphates; FBS -fetal bovine serum; GSTP1 -glutathione S-transferase pi 1; HOXA1 -homeo box A1; HOXA5-homeo box A5; HSP-27 -heat shock 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In this study, the starting concentration selected for testing was 25 nmol/L for both taxanes, since it was in the pharmacological range and a concentration that were shown by previous in vitro studies to have cytotoxic effects on breast cancer cells. [11][12][13][14][15][16][17][18][19][20] According to this, the final concentrations of the diluted solutions in our culture conditions equate to approximately molar concentrations of 12.5 Â 10 À17 , 12.5 Â 10 À21 and 12.5 Â 10 À41 mol/L for both taxanes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this study, the starting concentration selected for testing was 25 nmol/L for both taxanes, since it was in the pharmacological range and a concentration that were shown by previous in vitro studies to have cytotoxic effects on breast cancer cells. [11][12][13][14][15][16][17][18][19][20] According to this, the final concentrations of the diluted solutions in our culture conditions equate to approximately molar concentrations of 12.5 Â 10 À17 , 12.5 Â 10 À21 and 12.5 Â 10 À41 mol/L for both taxanes.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown that the concentrations within the range of µmol/L to nmol/L of these drugs could alter mRNA and microRNA expression levels of various genes in cancer cells in vitro. [11][12][13][14][15][16][17][18] The studies demonstrated that most mRNAs and microRNAs were either up-regulated or down-regulated in a concentration-and time-dependent manner by taxane treatment of various cancer cell lines including human breast cancer cell line MCF-7. Given the knowledge that many genetic regulatory reactions occur at extremely low concentrations, gene expression data from tumor cells treated with extremely low doses or high dilution of taxanes may provide useful suggestions about biological responses of cells to anti-cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having improved our knowledge of cancer biology notwithstanding, treatment of breast cancer has remained a challenging issue [ 5 7 ]. Of interest, the molecular anomaly of breast cancer cells cannot be explained via the genetic background as a result of the frequent sporadicity associated with the cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%